On the Strategic Directions of the EEU Development - S. Y. Glazyev (Евразийская интеграция: экономика, право, политика, 2020)
The article analyzes the reasons for incomplete integration processes, substantiates proposals for their elimination and further development of integration, based on the goals set by the heads of EEU states in the Declaration on the further development of integration processes within the EEU.The priority task of EEU further development is to complete a full-fledged Common economic space in a timely manner and start implementing a common policy for industry, agriculture, energy, transport and infrastructure, and finance. The system of measures necessary for improving the activities of the Eurasian economic Commission and ensuring high efficiency of the EEU common market regulation and its advanced development is considered.